La fotografia di danza nei primi decenni del Novecento - Samantha Marenzi (Drammaturgia, 2022)
What is dance photography? How was it born? How does it develop? How can we study it? Articulated around these questions, this contribution aims at identifying a field and a methodology of study, as well as tracing through some emblematic examples the genesis of an expressive language. Different from the portrait of the dancers and from stage photography, dance photography is configured at the crossroads between different genres such as the nude, the shooting of movement, the staged photography, the tableau vivant. From these visual traditions it takes on the techniques and problems and relaunches them in terms of the relationship between still image and expressive body, which provides new answers to questions stratified over time and history.